Small Business in Rostov-on-Don – Current Situation (the I quarter 2015) ("Journal "U". Economy. Management. Finance.", 2016)
The current state of development of business entities has contradictory character. The existing mutual sanctions have allowed some activity categories to show impressive results, but, at the same time, have led to the catastrophic closing of the whole business branches. A special pilot survey of representatives of small business of the million-plus city of Rostov-on-Don has been conducted in order to specify the situation.